The Effect of Social Capital on Knowledge Management Processes (Mazandaran University of Medical Sciences) - Ali Molaiy Eil Zolh; Elham Shah Bahrami; Mohammad Nasiri (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Social capital as a network of communication and mutual trust in the organization plays a crucial role in the production and creation of knowledge. Therefore, the present study aims to investigate the effect of social capital on knowledge management processes in Mazandaran University of Medical Sciences. Methods: This is a descriptive-analytical study conducted on a cross-sectional basis in 2016. The statistical population of the study comprised all the staff (faculty and administrative members) of this university (N = 230). The questionnaires were distributed among them and 183 questionnaires were collected. The data were collected via the Social Capital Questionnaire (17 questions) and Lawson Knowledge Management Questionnaire (24 questions). Data were analyzed using statistical tests (t), path coefficients (β), SPSS22 software and structural equation technique using SMART PLS software. Results: The results of t-test statistics (0.60, 0.61, 0.60, 0.61, 0.59 and 0.41) and path coefficients of β (7.32, 21.76, 21.6, 6.7, 14.49, and 2.9), respectively showed that social capital positively and significantly affect knowledge management processes (knowledge creation, knowledge absorption, knowledge organization, knowledge storage, knowledge dissemination, and knowledge utilization). Conclusion: The officials of such social institutions are recommended to identify, improve and strengthen social capital and its dimensions in order to enhance the knowledge management processes and provide them with a sustainable competitive advantage compared with other universities.